REFLECTION TO GUIDE MEDICAL STUDENTS’ SELFINTROSPECTION AND DEVELOPMENT: A QUALITATIVE REPORT - Imelda Ritunga; Etha Rambung (Jurnal Pendidikan Kedokteran Indonesia, 2020)
Background: Reflection is needed by the doctor in interpreting his experience, realizing its limitations so that it will be lifelong learning. In medical learning, self reflection can motivate students to realize their limitations and learn better. The purpose of this study is to explore the experiences of students in reflection learning. Methods: the research method uses a qualitative type with the research subjects being 15 first-year medical students. Reflection is taught at the beginning of education and is practiced in innovation design courses by providing weekly writing self-reflection assignments. The experience of writing self reflection was explored through group interviews (FGD) and in-depth interviews. Open questions are given to students, the results of interviews are verbatim and coding. This study has obtained ethical clearance.